2015
DOI: 10.1007/s13340-015-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of SIRT1 in myeloid cells impairs glucose metabolism with enhancing inflammatory response to adipose tissue hypoxia

Abstract: Chronic inflammation is a pathophysiology of insulin resistance in metabolic diseases, such as obesity and type 2 diabetes. Adipose tissue macrophages (ATMs) play important roles in this inflammatory process. SIRT1 is implicated in the regulation of glucose metabolism in some metabolic tissues, such as liver or skeletal muscle. This study was performed to investigate whether SIRT1 in macrophages played any roles in the regulation of inflammation and glucose metabolism. Myeloid cell-specific SIRT1-knockout mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Total RNA was isolated from BAT and ingWAT using the RNeasy® mini kit (Qiagen, Germany), and the cDNA synthesis and qPCR analysis were performed as described previously 8 , 9 , 34 , 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from BAT and ingWAT using the RNeasy® mini kit (Qiagen, Germany), and the cDNA synthesis and qPCR analysis were performed as described previously 8 , 9 , 34 , 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative Real-Time PCR Total RNA was extracted using the RNeasy Mini kit (Qiagen). Quantitative RT-PCR was performed, as described previously (29). For each gene, mRNA expression was calculated relative to the b-actin expression level or relative to the Gtf2b expression level and was presented as a value relative to that for control mice.…”
Section: Glucose Tolerance Test and Insulin Tolerance Testmentioning
confidence: 99%
“…Flow cytometry was performed as described previously (29). Cells in SVF were incubated with 2.4G2 (BD Biosciences), followed by the primary antibodies or matching control isotypes.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, our findings suggested a role of SIRT1 in mediating the effect of UnAG on NOS2 expression as, simultaneously, UnAG tended to decrease NOS2 but increased SIRT1 activity in the absence of EX527. In vitro study has revealed that SIRT1 deletion elevated the expressions of two hypoxia-responsive genes, interleukin 1β and NOS2 (Takikawa et al, 2016 ). Hypoxia is a fundamental pathology for ischemic-reperfusion diseases including pressure ulcers (Zhao et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%